Analisis Kinerja Finansial Pemerintah Kabupaten Sekadau Periode 2019-2022 - Andrianus, Andrianus; Hijriah, Amanah; Astarani, Juanda (Politeknik Negeri Ambon, 2024)
The purpose of this study was to measure and assess the financial performance of the Sekadau Regency Regional Government for the 2019-2022 period based on regional revenue realization data. Analysis of the financial performance of the Sekadau Regency Regional Government is measured by financial ratios. The financial performance of the Sekadau district local government can be measured by financial ratios, namely the degree of decentralization, the regional financial dependency ratio and the regional independence ratio. Qualitative research is the type of this research. Sekadau Regency Regional Revenue Realization data for the 2019-2022 period is the secondary data used in this study. The data was obtained using documentation techniques.Â The results showed that the financial performance of the Sekadau Regency Regional Government for the 2019-2022 period was measured based on the value of the degree of decentralization in the very bad category, the ratio of regional financial dependency in the very high category and the ratio of regional independence illustrating an instructive relationship pattern. Â